The impact of the numbered head together learning model assisted by interactive media on elementary students’ natural and social sciences learning outcomes - Tristaningrat, Made Adi Nugraha; Suastra, I Wayan; Jampel, Nyoman; Margunayasa, I Gede; Sanjaya, Dewa Bagus (Edelweiss Applied Science and Technology, 2024)
Indonesian elementary school students’ low learning outcomes in Natural and Social Sciences subjects is a problem that needs to be solved. Appropriate learning models and teaching media can improve students’ Natural and Social Sciences achievements. Thus, this study aims to evaluate the effectiveness of the Numbered Head Together learning model assisted by interactive media and class students in enhancing learning outcomes in Natural and Social Sciences subjects. This study involved 34 students, 18 of whom were in the control class and 16 of whom were in the experimental class. The study data were collected using a post-test to measure students’ learning outcomes. The collected data were analyzed using an independent t-test. The results of this study show that there are differences in the learning outcomes of experimental and control class students; this is evidenced by the results of the t- test, the value obtained by the results on equal variances assumed. The sig value. (2-tailed) obtained in equal variances, assumed to be 0.002, so sig. (2-tailed) = 0.002 <0.05, so there are differences in the students’ natural and social sciences learning outcomes of experimental and control classes. Since the students’ learning outcomes in the experimental class are better than those in the control class, this study concludes that the Numbered Head Together learning model assisted by interactive media significantly affects students’ Natural and Social Sciences subject learning outcomes.